1999
DOI: 10.1161/01.cir.99.18.2378
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Prediction in Cardiac Surgery Patients

Abstract: In our experience, the Parsonnet score performs very well, with calibration and discrimination very high, better than general severity systems, and it is an appropriate tool to assess mortality in cardiac surgery patients. In our experience, the general severity systems perform well to predict mortality after cardiac surgery, with high calibration of MPM II24, MPM II0, and SAPS II; minor calibration for APACHE II; and high discrimination for 3 general systems, but not as well as the Parsonnet score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 26 publications
(12 reference statements)
0
16
0
1
Order By: Relevance
“…Finally, we decided to include patients admitted after heart surgery in the case mix, since those patients are taken into account in the SAPS 3 admission score. In addition, previous studies showed that performance of the APACHE II and SAPS II is adequate in case mix of patients admitted to the ICU after heart surgery [12]. Additional information on exclusion criteria may be found in the electronic supplementary material (ESM).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we decided to include patients admitted after heart surgery in the case mix, since those patients are taken into account in the SAPS 3 admission score. In addition, previous studies showed that performance of the APACHE II and SAPS II is adequate in case mix of patients admitted to the ICU after heart surgery [12]. Additional information on exclusion criteria may be found in the electronic supplementary material (ESM).…”
Section: Methodsmentioning
confidence: 99%
“…Use of a single site is also a limitation because it can decrease the generalizability of the study findings. Inclusion of the APACHE II variable for the entire sample may also be a limitation, because the APACHE II is a poor prognostic indicator among cardiac surgery patients [47][48][49] ; consequently, we eliminated this variable from the main analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…It must be noted that the risk scoring system used here was originally devised for assessment of operative mortality in acquired adult heart disease. 18 More recent evidence has identified the Parsonnet score as being among the best predictive systems not only for hospital mortality 26 but also for hospital morbidity after adult cardiac operations. 19 On the basis of the work of Lawrence and colleagues, 19 who demonstrated a direct correlation between Parsonnet score and prevalence of perioperative complications, a choice was made to condense the risk categories into low (1% to 5%) and high (Ͼ9%) risk and to stratify postoperative morbidity accordingly.…”
Section: I-256 Circulation September 18 2001mentioning
confidence: 99%